Malay Version of Asthma Knowledge Questionnaire: A Validation and Reliability Study - Akmar Mohamad, N. Fafwati Faridatul; Musa, Azizah; Derani, Faridah; Mesiran, Nor Khamizah; Kassim, Asiah; Mohd Hairi, Farizah; Zainuddin, Hafizah (Malaysian Journal of Medicine and Health Sciences, 2023)
Introduction: The Asthma Knowledge Questionnaire developed by C. Rodriguez Martinez in 2005 was proved to be a valid instrument for asthma knowledge assessment for parents of children with asthma. 17 items were included in the questionnaire including their myths and beliefs, knowledge, and associated aspects. The objective of this study is to analyse the validity and reliability of the Malay version of the questionnaire. Methods: Forward-Backward translation method was used by language experts to obtain the Malay version of the questionnaire. The questionnaire was then given to twenty respondents at the Paediatric Institute Hospital Kuala Lumpur to ensure the clarity and relevance of the questionnaire as a pilot study. Subsequently, 60 respondents who fulfilled the inclusion and exclusion criteria were selected to proceed with the reliability test of the Malay version questionnaire. The results were analysed with SPSS version 26.0. The reliability and internal consistency were confirmed by intra-class correlation and Cronbach’s alpha coefficient. Results: There were 60 respondents to the questionnaire consisting of parents and caretaker who has child with asthma at the Institute of Paediatric Hospital Kuala Lumpur. The mean age of respondents was 34 ± 7.5year old. 91.7% of the respondents were female. The overall Cronbach’s alpha coefficient of the questionnaire was 0.84. Conclusion: The Malay version of the Asthma Knowledge Questionnaire has a good degree of validity, reliability and is culturally acceptable equivalent to the original version. REFERENCES Ferrante G, La Grutta S. The burden of pediatric asthma. Frontiers in pediatrics. 2018 Jun 22;6: 186. [Google Scholar] [Pubmed] [PMC Free Article] [Crossref] Asher MI, Montefort S, Björkstén B, Lai CK,Strachan DP, Weiland SK, Williams H, ISAACPhase Three Study Group. Worldwide time trendsin the prevalence of symptoms of asthma, allergicrhinoconjunctivitis, and eczema in childhood:ISAAC Phases One and Three repeat multicountrycross-sectional surveys. The Lancet. 2006 Aug26;368(9537):733-43. doi: 10.1016/S0140-6736(06)69283-0.[<a href="https://scholar.google.com/scholar_lookup?title=Worldwide+time+trendsin+the+prevalence+of+symptoms+of+asthma%2C+allergicrhinoconjunctivitis%2C+and+eczema+in+childhood%3AISAAC+Phases+One+and+Three+repeat+multicountrycross-sectional+surveys&btnG=">Google Scholar][Pubmed] Zaman M, Ashraf S, Javaid M. Reliability of diagnosis and asthma knowledge, attitudes and perception (KAP) in rural population of NWFP, Pakistan. Pakistan Journal of Chest Medicine. 2015 Jun 18;12(4).[Google Scholar] Ponieman D, Wisnivesky JP, Leventhal H, Musumeci-Szabó TJ, Halm EA. Impact of positive and negative beliefs about inhaled corticosteroids on adherence in inner-city asthmatic patients. Annals of Allergy, Asthma & Immunology. 2009 Jul 1;103(1):38-42. doi: 10.1016/S1081-1206(10)60141-X.[<a href="https://scholar.google.com/scholar_lookup?title=Impact+of+positive+and+negative+beliefs+about+inhaled+corticosteroids+on+adherence+in+inner-city+asthmatic+patients.+Annals+of+Allergy%2C+Asthma+%26+Immunology&btnG=">Google Scholar][Pubmed][Crossref] Luckie K, Pang TC, Kritikos V, Saini B, Moles RJ. Development and validation of an asthma first aid knowledge questionnaire. Research in Social and Administrative Pharmacy. 2018;14(5):459-63. doi: 10.1016/j.sapharm.2017.05.014.[Google Scholar][Pubmed] Norzila MZ, Haifa AL, Deng CT, Azizi BH. Prevalence of childhood asthma and allergy in an inner-city Malaysian community: intra- observer reliability of two translated international questionnaires. The Medical journal of Malaysia. 2000;55(1):33-9.[<a href="https://scholar.google.com/scholar_lookup?title=Prevalence+of+childhood+asthma+and+allergy+in+an+inner-city+Malaysian+community%3A+intra-+observer+reliability+of+two+translated+international+questionnaires&btnG=">Google Scholar][Pubmed] Martínez CR, Sossa MP. Validation of an asthma knowledge questionnaire for use with parents or guardians of children with asthma. Archivos de Bronconeumología (English Edition). 2005 Aug 1;41(8):419-24. doi: 10.1016/S1579- 2129(06)60256-5[Google Scholar][Pubmed][Crossref] AlOtaibi E, AlAteeq M. Knowledge and practice of parents and guardians about childhood asthma at King Abdulaziz Medical City for National Guard, Riyadh, Saudi Arabia. Risk management and healthcare policy. 2018; 11:67-75. doi: 10.2147/ RMHP.S143829[<a href="https://scholar.google.com/scholar_lookup?title=Knowledge+and+practice+of+parents+and+guardians+about+childhood+asthma+at+King+Abdulaziz+Medical+City+for+National+Guard%2C+Riyadh%2C+Saudi+Arabia.+Risk+management+and+healthcare+policy&btnG=">Google Scholar][PMC free article] [Pubmed] Espinosa L, AM SS. The Spanish version of the Newcastle Asthma Knowledge Questionnaire for parents of children with asthma (NAKQ). Transcultural adaptation and reliability analysis. Anales De Pediatria (Barcelona, Spain: 2003) 2009;70(3):20917.doi:10.1016/j.anpedi.2008.10.013[<a href="https://scholar.google.com/scholar_lookup?title=The+Spanish+version+of+the+Newcastle+Asthma+Knowledge+Questionnaire+for+parents+of+children+with+asthma+%28NAKQ%29.+Transcultural+adaptation+and+reliability+analysis&btnG=">Google Scholar][Pubmed] Hallit S, Raherison C, Waked M, Salameh P. Validation of asthma control questionnaire and risk factors affecting uncontrolled asthma among the Lebanese children’s population. Respiratory medicine. 2017; 122:51-7. doi: 10.1016/j. rmed.2016.11.018.[<a href="https://scholar.google.com/scholar_lookup?title=Validation+of+asthma+control+questionnaire+and+risk+factors+affecting+uncontrolled+asthma+among+the+Lebanese+children%E2%80%99s+population&hl=en&as_sdt=0,5">Google Scholar][Pubmed][Crossref] Simba J, Marete I, Waihenya R, Kombe Y, Mwangi A, Mburugu P, Ogaro F. Knowledge and perceptions on childhood asthma among care-takers of children with asthma at a National Referral Hospital in Western Kenya: a descriptive study. African health sciences. 2018;18(4):965-71. doi: 10.4314/ahs.v18i4.16.[<a href="https://scholar.google.com/scholar_lookup?title=Knowledge+and+perceptions+on+childhood+asthma+among+care-takers+of+children+with+asthma+at+a+National+Referral+Hospital+in+Western+Kenya%3A+a+descriptive+study&btnG=">Google Scholar][Pubmed] Household Income & Basic Amenities Survey Report 2019. Available from https://www.dosm. gov.my/v1.[Google Scholar] Pallant, Julie. 2010. SPSS survival manual – A step by step guide to data analysis using SPSS, 4th ed. Allen & Unwin[Google Scholar] Szefler SJ, Chmiel JF, Fitzpatrick AM, Giacoia G, Green TP, Jackson DJ, Nielsen HC, Phipatanakul W, Raissy HH. Asthma across the ages: knowledge gaps in childhood asthma. Journal of Allergy and Clinical Immunology. 2014;133(1):3-13.doi: 10.1016/j.jaci.2013.10.018.[Google Scholar][Pubmed][Crossref] The Third National Health and Morbidity Survey (NHMS III) 2006. Institute for Public Health (IPH). Malaysia: Ministry of Health; 2008. Available from https://iku.moh.gov.my/images/IKU/Document/ REPORT/2006/ExecutiveSummary.pdf World Health Organization [Internet]. Asthma; 2021 [cited 2021 May]. Available from: https:// www.who.int/news-room/fact-sheets/deatil/ asthma Praena-Crespo M, Aquino-Llinares N, Fernandez- Truan JC, Castro-Gomez L, Segovia-Ferrera C. Asthma education taught by physical education teachers at grade schools: a randomised cluster trial. Allergologia et immunopathologia. 2017; 45(4):375-86. doi: 10.1016/j.aller.2016.10.022.[Google Scholar][Pubmed][Crossref] Urrutia-Pereira M, Mocellin LP, de Oliveira RB, Simon L, Lessa L, Solé D. Knowledge on asthma, food allergies, and anaphylaxis: Assessment of elementary school teachers, parents/caregivers of asthmatic children, and university students in Uruguaiana, in the state of Rio Grande do Sul, Brazil. Allergologia et immunopathologia. 2018; 46(5):421-30. doi: 10.1016/j.aller.2017.09.018.[<a href="https://scholar.google.com/scholar_lookup?title=Knowledge+on+asthma%2C+food+allergies%2C+and+anaphylaxis%3A+Assessment+of+elementary+school+teachers%2C+parents%2Fcaregivers+of+asthmatic+children%2C+and+university+students+in+Uruguaiana%2C+in+the+state+of+Rio+Grande+do+Sul%2C+Brazil&btnG=">Google Scholar][Pubmed][Crossref] Lawson JA, Brozek G, Shpakou A, Fedortsiv O, Vlaski E, Beridze V, Rennie DC, Afanasieva A, Beridze S, Zejda J. An international comparison of asthma, wheeze, and breathing medication use among children. Respiratory medicine. 2017;133:22-8.doi: 10.1016/j.rmed.2017.11.001.[Google Scholar][Pubmed][Crossref] Bisgaard H, Szefler S. Prevalence of asthma- like symptoms in young children. Pediatric pulmonology. 2007;42(8):723-8. doi: 10.1002/ ppul.20644.[Google Scholar][Pubmed] 2021 GINA Report, Global Strategy for Asthma Management and Prevention. Available at https:// ginasthma.org/gina-reports/ Omar AH. Respiratory symptoms and asthma in primary school children in Kuala Lumpur. Pediatrics International. 1990;32(2):183-7. doi: 10.1111/j.1442-200x.1990.tb00807.x.[Google Scholar][Pubmed] International Study of Asthma and Allergies in Childhood (ISAAC) Steering Committee. Worldwide variations in the prevalence of asthma symptoms: the International Study of Asthma and Allergies in Childhood (ISAAC). Eur Respir J. 1998;12(2):315-35. doi: 10.1183/09031936.98.12020315.[Google Scholar][Pubmed] Glazebrook C, McPherson AC, Macdonald IA, Swift JA, Ramsay C, Newbould R, Smyth A. Asthma as a barrier to children’s physical activity: implications for body mass index and mental health. Pediatrics. 2006;118(6):2443-9. doi: 10.1542/peds.2006-1846.[<a style="background-color: #ffffff; font-size: 0.875rem;" href="https://scholar.google.com/scholar_lookup?title=Asthma+as+a+barrier+to+children%E2%80%99s+physical+activity%3A+implications+for+body+mass+index+and+mental+health.+Pediatrics&btnG=">Google Scholar][Pubmed]